Impact of Underweight after Treatment on Prognosis of Advanced-Stage Ovarian Cancer - Se Ik Kim; Hee Seung Kim; Tae Hun Kim; Dong Hoon Suh; Kidong Kim; Jae Hong No; Hyun Hoon Chung; Yong Beom Kim; Yong Sang Song (Journal of Immunology Research)
This study aimed to investigate the impact of underweight status on the prognosis of advanced-stage ovarian cancer. A total of 360 patients with stage III-IV epithelial ovarian cancer were enrolled and divided into three groups by body mass indexes (BMIs): underweight (BMI < 18.5 kg/m2); normal weight to overweight (18.5 kg/m2 BMI < 27.5 kg/m2); obesity (BMI ≥ 27.5 kg/m2). Progression-free survival (PFS), overall survival (OS), CA-125, and neutrophil to lymphocyte ratio (NLR) as a marker reflecting host inflammation and immunity were compared among the three groups according to the three treatment times: at diagnosis; after surgery; and after treatment. Only underweight status after treatment was associated with poor OS in comparison with normal weight to overweight or obesity (mean value, 44.9 versus 78.8 or 67.4 months; P=0.05); it was also an unfavorable factor for OS (adjusted HR, 2.29; 95% CI, 1.08–4.85). Furthermore, NLR was higher in patients with underweight than in those with obesity after treatment (median value, 2.15 versus 1.47; P=0.03), in spite of no difference in CA-125 among the three groups at the three treatment times. In conclusion, underweight status after treatment may be a poor prognostic factor in patients with advanced-stage ovarian cancer, which accompanies increased host inflammation and decreased immunity.